Configuration of the Late Paleoproterozoic supercontinent Columbia: Insights from radiating mafic dyke swarms - Hou, Guiting; Santosh, M.; Qian, Xianglin; Lister, Gordon S.; Li, Jianghai (Gondwana Research, 2008)
Remnants of 2.1-1.8 Ga orogens can be recognized in nearly every craton assembled within reconstructions of the Rodinia supercontinent, although no particular pattern of laterally extensive orogenic belts emerges. These cratons may be the fragments of an older supercontinent formed in response to the collision and accretion of even older cratons during the early Earth history. Paleomagnetic constraints have played a limited role in many previous reconstructions of the early Precambrian supercontinent mainly because of the poor age. control and a large scatter of the paleomagnetic poles. The geometry of giant radiating dyke swarms and orogenic belts provide important constraints for the reconstruction of the Pre-Rodinian supercontinent. Some early unmetamorphosed and undeformed mafic dyke swarms in North China, Southern Peninsular India and North America share coeval age of similar to 1.85 Ga. If these continents are assembled, the overall pattern exhibited by the mafic dyke swarms appears to constitute a giant radiating swarm, with a piercing point between the Cuddapah rift in South India and the Xiong'er aulacogen in North China. This suggests that the North China Craton, Indian Craton and Canadian Shield may be fragmented from the same landmass. The reconstruction of similar to 1.85 Ga giant radiating dyke swarm attempted in this paper suggests that the North China Craton, India Craton and Canadian Shield were united together to form a landmass within the Columbia supercontinent before its extension and break-up. The 1.90-1.85 Ga Andean-style North Orogenic Belt suggests that a subduction zone existed on the northern margin of the North China Craton. Wopmay Orogenic Belt developed in a 1.88-1.84 Ga continental volcano-plutonic arc, which is interpreted as the product of eastward subduction of oceanic lithosphere. The Transantarctica Orogenic Belt in East Antarctica may be another candidate to be linked with the subduction zone. The North Orogenic, Wopmay Orogenic and Transantarctica Orogenic Belts could be connected to form a continuous subduction zone. The orogenic comparison strengthens the configuration of the Columbia supercontinent proposed by the reconstruction of the giant radiating dyke swarm. The Laurentia, West Australia and East Antarctica were relatively stable from 1.85 Ga to 1.20 Ga as inferred from the data on dyke swarms, magmatism and the paleomagnetism. These continents constituted the core of the Columbia supercontinent in the Late Paleoproterozoic time. The North China Craton and Indian Craton were however separated from the Columbia supercontinent during the Mesoproterozoic time. (C) 2008 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000258812500009&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Geosciences, Multidisciplinary SCI(E) 171 REVIEW 3 395-409 14